Improved Basic Locomotor Movements of Children through the Multiple Intelligence-Based Perceptual Motor Activity Model - Yudanto Yudanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Kindergarten is a period of basic movement development. Basic locomotor movements are the basis of various skills that require training and guidance that will be able to develop in the child so that the child can perform well. This study aimed to determine the improvement of basic locomotor movements of kindergarten children through motor perception activities based on multiple intelligence. This research is pre-experimental research, with a one-group pre-test and post-test design. The subjects of this research were 2kindergarten’s students. The research instrument used the Test of Gross Motor Development-2 (TGMD-2) from Ulrich (2000). Data analysis used the t-test, by comparing the average pre-test results with the average post-test results. The results of the research on basic locomotor movements, which include: run, gallop, hop, leap, horizontal jump, and slide, show the value of sig. 0.000 0.05 and there was an increase in the post-test mean of each basic locomotor movement. The application of the model of perceptual motor activity based on multiple intelligences can improve basic locomotor movements, so kindergarten teachers can apply the model of perceptual motor activity based on multiple intelligences to improve basic locomotor movements.